Two-Dimensional Numerical Simulation of Detonation Transition with Multi-Step Reaction Model: Effects of Obstacle Height. Issue 4 (3rd April 2019) - Ago, Ayu; Tsuboi, Nobuyuki; Dzieminska, Edyta; Hayashi, A. Koichi
ABSTRACT: The numerical simulations on DDT (Deflagration-to-Detonation Transition) in the two-dimensional channel with the repeated obstacles using multi-step reaction model are performed for various BR values (Blockage Ratio: the value obtained by dividing the height of the obstacles by the channel width). This research intends to find out more detailed mechanisms of the detonation transition in channels with obstacles in order to understand deeply the physical phenomena such as shock wave, turbulent flame, and local explosion caused by self-ignition. In the channel with repeated obstacles, filled with a stoichiometric premix gas of hydrogen/oxygen a small energy source near the left end of the channel is located as an initial ignition source. As a result, for BR = 0.3 and 0.45, the deflagration transits to detonation, and the flame is largely disturbed. Then the flame is accelerated by the repeated local explosions, the compression and expansion in the flow path, as well as strengthened shock wave. It is found that the onset of DDT has a different dependence on the height of obstacles. Also, even when local explosions occur, the detonation transition can fail, and for BR = 0.45 the detonation transition is delayed comparing with BR = 0.3 due to obstacles height.